EARLY WARNING INDICATORS OF DEFAULTS IN THE BANKING SYSTEM OF UKRAINE - Kornyliuk, Roman (Journal of European Economy, 2017)
We construct and explore a new quarterly dataset of 12 traditional financial ratios for defaulted banks. The retrospective comparative analysis of bankspecific early-warning indicators’ predictive power for 2 samples of problem banks over 2008–2012 and 2014 periods was conducted. The survey results reveal the most appropriate early-warning signals, which are useful for credit rating methodologies, and can improve the quality of systemic risk monitoring in the banking sector. The best predictors of defaults proved to be traditional indicators of profitability and liquidity, the share of retail deposits in the liabilities, and qualitative factor of the bank's ownership structure. Insufficiently indicative predictive ability was demonstrated by the simplified indicators of capital adequacy and assets quality.